POLA PARENTING DAN PENGARUHNYA TERHADAP GAYA BELAJAR ANAK - Siti Khasinah; Elviana Elviana (Prodi PGMI FTK UIN Ar-Raniry Banda Aceh, 2023)
This recent study explores the impact of parenting styles on the learning styles of students of a raudhatul athfal in Aceh. Eleven parents of the students were taken as research sample and to whom a list of questionnaires was distributed. The questionnaire consisted of 20 questions related to parenting styles, while the other 34 related to learning styles. The results of the research were then analyzed using linear regression statistical formula to see if there was influence of parenting styles on students’ styles in learning. The findings show that the majority of parents carry out authoritative parenting, a few are authoritarian, but none use a permissive way. Besides, it is found that most of children are visual learners, some are auditory and a few are kinesthetic. Of the three children's learning styles, the visual style gets the most dominant influence from parenting, followed by the auditory learning style, and the least is the kinesthetic style.